The Influence of Media on the State Supervision System - Muhammad Abrar Azizi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
Dayah is the oldest dakwah development institution in the archipelago, which emphasizes the formation of community morals to be civilized and polite. At first the dayah was not only a place for community religious learning, but also as a school institution to study general education, but when colonialism took place in this country, education was divided into two categories, namely religion and general. From then on, the effect of the decline in dayah education occurred, so that the interest of the community to study in the dayah was reduced and the function of the dayah began to change from its existence. Dayah institutions exist in society, and are community-owned educational institutions, which are built and developed by the community themselves independently. Dayah institutions are still consistent with religious education, so that this becomes a distinctive feature for dayah which is different from other educational institutions. Dayah has a special education system and pattern that is arranged in the form of a curriculum that is taught to its students. This learning pattern aims to be able to give birth to future generations who have strong faith and have broad insight.